2012
DOI: 10.5897/ajb11.3186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spermidine, proline and carbohydrate sources on somatic embryogenesis from main root transverse thin cell layers of Vietnamese ginseng (Panax vietnamensis Ha et. Grushv.)

Abstract: The in vitro main roots transverse thin cell layers of Vietnamese ginseng (Panax vietnamensis Ha et. Grushv.) were cultured on Murashige and Skoog (MS) medium supplemented with 1.0 mg.l -1 2,4dichlorophenoxyacetic acid (2,4-D), 0.2 mg.l -1 kinetin and 0.5 mg.l -1 naphthaleneacetic acid (NAA), 30 g.l -1 sucrose and 8.5 g.l -1 agar to establish embryogenic culture. The effects of exogenous spermidine and proline on enhancement of somatic embryogenesis was investigated. The results show that spermidine (0.1 mM) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
2
1
0
2
Order By: Relevance
“…This is consistent with the result of a previous study on P. ginseng [26]. However, the mean number of somatic embryos and EFC index decreased at sucrose concentrations above 7%, which is similar to the result reported for P. vietnamensis [15]. The negative effects of excessive sucrose concentrations have also been reported in other plant species [40,41].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with the result of a previous study on P. ginseng [26]. However, the mean number of somatic embryos and EFC index decreased at sucrose concentrations above 7%, which is similar to the result reported for P. vietnamensis [15]. The negative effects of excessive sucrose concentrations have also been reported in other plant species [40,41].…”
Section: Discussionsupporting
confidence: 92%
“…We found that the carbon source greatly affected somatic embryogenesis in P. ginseng (Table 1 and Figure 2); somatic embryo induction was greatest in culture medium supplemented with sucrose. A similar finding was observed by Nhut et al [15] in the callus culture of P. vietnamensis (Vietnamese ginseng), who found that sucrose had a greater embryogenic effect than glucose and fructose. Several studies have suggested that sucrose is the best choice for cell growth and embryogenesis in many species [35,36].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Данные об успешном микроразмножении корейского женьшеня (Panax ginseng C.A. Meyer) и других видов женьшеня стимулировали исследования культуры тканей женьшеня Ngoc Linh, в частности изучение органогенеза (5), формирования искусственных семян (6), образования микроризомов (7), соматического эмбриогенеза (8)(9)(10)(11)(12). Некоторые работы были сосредоточены на культурах вторичных и придаточных корней (13) для производства биомассы женьшеня Ngoc Linh с целью получения гинсенозидов (14)(15)(16)(17)(18).…”
unclassified
“…В исследовании D. Nhut с соавт. (9), соматический эмбриогенез был индуцирован в культуре in vitro на основе тонкого слоя клеток основного корня. Однако, выживаемость проростков после переноса в питомник оказалась довольно низкой, поэтому считается, что методы in vitro все еще не обеспечивают стабильного размножения женьшеня Ngoc Linh.…”
unclassified